1948
DOI: 10.1152/ajplegacy.1948.153.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orally Administered Urea on the Ammonia and Urea Concentration in the Blood of Cattle and Sheep, With Observations on Blood Ammonia Levels Associated With Symptoms of Alkalosis

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1954
1954
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Subclinical toxicity may alter carbohydrate metabolism in the liver and energetic effi ciency of lactation (Owens and Bergen 1983 ). Dinning et al ( 1948 ) observed that a single dose of 116 g of urea caused ataxia, severe tetany, a retarded respiration rate, and excessive salivation in cattle. Hart et al ( 1939 ) found that cattle fed for a year with a ration containing 4.3 % urea showed hypertrophy of the kidneys upon slaughter, but there was no evidence of toxicity.…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…Subclinical toxicity may alter carbohydrate metabolism in the liver and energetic effi ciency of lactation (Owens and Bergen 1983 ). Dinning et al ( 1948 ) observed that a single dose of 116 g of urea caused ataxia, severe tetany, a retarded respiration rate, and excessive salivation in cattle. Hart et al ( 1939 ) found that cattle fed for a year with a ration containing 4.3 % urea showed hypertrophy of the kidneys upon slaughter, but there was no evidence of toxicity.…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…This presentation shows marked similarities to phalaris cardiac 'sudden death' syndrome and related syndromes. The sequence of cellular events causing death in these cases is thought to be multi-factorial, potentially via ammonia perturbation of the lactic acid cycle [54], or inhibition of sodium-potassium ATPase pump recycling of extracellular potassium causing systematic metabolic acidosis [55] resulting in subsequent cardiac arrest [53]. Interestingly, altered lactic acid cycling can also result in altered neurological signs, coincident with changes observed in livestock with a PE-like syndrome, suggesting that these two syndromes may not be totally unrelated.…”
Section: Cardiac and Pe-like Sudden Death: A Variation In Presentation Of One Clinical Syndrome?mentioning
confidence: 99%
“…(1) It is slowly hydrolysed in the rumen and consequently risks of ammonia poisoning are remote compared with urea (Dinning et al 1948;Gallup, Pope & Whitehair, 1953; study the comparative nutritional value of biuret and urea in maintenance and production diets of cattle. Observations were made under closely controlled pen conditions in an endeavour to accurately establish some basic principles relating to the utilization of these two compounds.…”
Section: Introductionmentioning
confidence: 99%